2000
DOI: 10.1128/aac.44.6.1680-1685.2000
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Responses to Different Antimalarial Drugs in Vivax Malaria

Abstract: The therapeutic responses to the eight most widely used antimalarial drugs were assessed in 207 adult patients with Plasmodium vivax malaria. This parasite does not cause marked sequestration, so parasite clearance can be used as a direct measure of antimalarial activity. The activities of these drugs in descending order were artesunate, artemether, chloroquine, mefloquine, quinine, halofantrine, primaquine, and pyrimethamine-sulfadoxine (PS). Therapeutic responses to PS were poor; parasitemias did not clear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
157
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(170 citation statements)
references
References 14 publications
11
157
1
1
Order By: Relevance
“…Although some recrudescences could result from inadequate drug absorption or unusual disposition kinetics, recurrent infections in this study were newly acquired infections or relapses. 26,27 The Pvmsp-3a polymorphism analysis has been an important molecular epidemiological tool for distinguishing P. vivax infections in malaria-endemic areas. 18,28,29 This study used Pvmsp-3a PCR-RFLP and TR-PCR analysis as tools for differentiating primary from subsequent P. vivax infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although some recrudescences could result from inadequate drug absorption or unusual disposition kinetics, recurrent infections in this study were newly acquired infections or relapses. 26,27 The Pvmsp-3a polymorphism analysis has been an important molecular epidemiological tool for distinguishing P. vivax infections in malaria-endemic areas. 18,28,29 This study used Pvmsp-3a PCR-RFLP and TR-PCR analysis as tools for differentiating primary from subsequent P. vivax infections.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Mefloquine, 43 atovaquone + proguanil, 44 halofantrine, 45 piperaquine, 46 artesunate, 47,48 and pyronaridine, 49 all show good efficacy against chloroquine-resistant (CQR) P. vivax in clinical trials.…”
mentioning
confidence: 99%
“…Nevertheless, quinine is not considered an ideal treatment owing to its toxicity. Furthermore, it was found that treatment of P. vivax infections with quinine might lead to early relapses owing to the short half-life of quinine [36].…”
Section: Plasmodium Malariaementioning
confidence: 99%
“…A treatment success of 100% has been reported [36]. Doxycycline monotherapy applied in 100 mg oral doses twice a day for 7 days shows poor cure rates in P. vivax infections [37], however quinine given in doses of 10 mg salt/kg three times a day for 7 days is also effective against CQ-resistant P. vivax strains [38].…”
Section: Plasmodium Malariaementioning
confidence: 99%